Heterologous Expression of Î±-Amylase from Saccharomycopsis fibuligera R64 and its Tyr401Trp Mutant in Pichia pastoris - RIEZKI AMALIA; WANGSA TIRTA ISMAYA; FERNITA PUSPASARI; KHOMAINI HASAN; TOTO SUBROTO; DESSY NATALIA; SOETIJOSO SOEMITRO (Microbiology Indonesia, 2016)
Î±-Amylase from Saccharomycopsis fibuligera R64 is a non-adsorbing raw-starch degrading enzyme, a unique characteristic. This character is difficult to explain in the absence of its three-dimensional structure. Here we discuss the expression of a-amylase from Saccharomycopsis fibuligera in Pichia pastoris and the effect of site directed mutagenesis on its activity. A model based on the structure of its homologs suggested mutation of codon of Tyr401 into that of a Trp residue. An activity study using whole cells P. pastoris showed similar substrate degradation rates by cells carrying either the native or mutant amylase encoding gene. However, the purified enzyme of the mutant strain showed faster starch hydrolysis.